Accuracy of Infrared Photodiode Sensors at The Flowrate Measurement in Infusion Device Analyzer with 2 Channel TFT Display - Azizah, Wafiq Nur; Rahmawati, Triana; Syaifudin, Syaifudin (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Infusion is a medical procedure involving the delivery of fluids, medications, nutrients, or other substances into a patient's circulatory system through intravenous flow. In its implementation, commonly used infusion tools are infusion pumps and syringe pumps, as these devices assist in accurately and precisely controlling the flow rate. However, with continuous usage, there is a potential for inaccuracies in measuring the flow rate of fluids from these devices. Therefore, periodic calibration is necessary. According to Regulation No. 54 of 2015 from the Ministry of Health, calibration of medical devices, including infusion devices, must be conducted at least once a year to ensure their ongoing accuracy. The purpose of this research is to design an Infusion Device Analyzer (IDA) with a flow rate parameter. The contribution of this research is that the tool can accurately calculate the correct value of the flow rate that comes out of the infusion pump and syringe pump. One of the innovations resulting from this study is the Infusion Device Analyzer, equipped with a 7-inch TFT LCD screen that displays graphical parameters of the flow rate. This is achieved through the use of Infrared Photodiode sensors, which measure the rate of fluid flow. The performance graph displayed on the TFT LCD can visualize the stability of fluid flow when using various types of devices like syringe pumps and infusion pumps. The results of this research show a range of error values in the performance of various brands of infusion devices. When using the Terumo Syringe Pump, there is an error value of 0.86% (100 mL/h) for Channel 1 and 0.69% (100 mL/h) for Channel 2. For the B-Braun Syringe Pump, the error value is 1.30% (100 mL/h) for Channel 1 and 0.85% (10 mL/h) for Channel 2.